Globalization and education : teaching, learning and leading in the world schoolhouse - Brooks, Jeffrey S., 1970-; Normore, Anthony H.; Brooks, Melanie C., 1972-; Sum, Nicola (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Globalization and Education: Teaching, Learning and Leading in the World Schoolhouse explores the various ways educators' work is influenced by globalization. This book presents topics and contexts traditionally marginalised in mainstream education research discourses and shows how local and global education issues are intersecting and shaping the ways in which ideas and practices are shared around the world. Each chapter presents an educational issue in an understudied international context, such as Saudi Arabia, Guyana, Bangladesh, Malaysia, Indonesia, Brazil, and Nepal. Topics range from how the knowledge industry shapes education in schools to the impact of globalisation on school leadership, teaching, and learning. We invite scholars and practitioners to join us in the world schoolhouse, a place where discussion about educational understanding and improvement is not bounded by national borders, school systems or language. This book will both challenge and expand thinking about the complexities of education during a time of globalisation and change"-- Provided by publisher.
Keywords: Education and globalization.; Multicultural education.; Education -- Aims & Objectives.; Globalization.; Educational strategies and policy.; elektronické knihy; electronic books